Avaliação da verticalização de segundo molar inferior ancorado em minimplante através da metodologia dos elementos finitos 3D - Kina, Juliana [UNESP] (2013)
Introduction: One of the problems caused by the loss of the first molar is mesial movement of the adjacent second molar, which can lead to problems occlusal and functional. The use of mini-implant anchorage has been recommended in the literature to recover the lost space, with satisfactory clinical performance. However, biomechanical studies well designed, with a high level of scientific evidence has not yet been verified. Thus, through biomechanical analysis, based on 3D finite element method, this study evaluated the stress distribution simulated model of molar uprighting with the use of a mini -implants as orthodontic anchorage device, which was submitted tensile strength lingual, buccal and associated (buccal and lingual). Methods: For this study it was made a three-dimensional finite element model, a block containing simulated mandibular posterior region with a second molar mesially angled at 30 degrees, and a self-drilling mini-implant of 1.5 x 2.0 x 8 mm, inserted the distal positioned vertically in relation to the molar angled approximately 10 mm apart. Results: The results were plotted in color maps, standardized, allowing qualitative comparison between the situations tested. The interpretation criteria were based on analyzes of general displacement maps, Maximum principal, and microstrain, each criterion separately described. Conclusion: It was found that the three types of load employed were effective for molar uprighting and that the application of force to the tooth tilted bilateral movement generates more uniform.